Characterization of Cu2O thin films with addition of additive prepared by sol-gel spin coating process - Dewi Suriani, Che Halin, Dr.; Ibrahim, Abu Talib; A. R., Daud; Muhammad Azmi, A. Hamid (Universiti Putra Malaysia, 2012)
Link to publisher's homepage at http://www.upm.edu.my/